2019
DOI: 10.1038/s41535-019-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous quantum oscillations and evidence for a non-trivial Berry phase in SmSb

Abstract: Topologically non-trivial electronic structures can give rise to a range of unusual physical phenomena, and the interplay of band topology with other effects such as electronic correlations and magnetism requires further exploration. The rare earth monopnictides X(Sb,Bi) (X = lanthanide) are a large family of semimetals where these different effects may be tuned by the substitution of rare-earth elements. Here we observe anomalous behavior in the quantum oscillations of one member of this family, antiferromagn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…This rare response of the oscillation amplitude as a function of temperature was not observed in other members of the LnAlP n family so far [31,33,35,41]. It was previously observed in just a few materials, such as the chargetransfer salts [58] and SmSb [59]. In the first case, the sudden decrease of the amplitude with decreasing temperature was associated with the presence of highly metallic edge states related to the quantum Hall effect in quasi-two-dimensional materials [58], which is unlikely to be the cause for the behavior found in CeAlSi.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…This rare response of the oscillation amplitude as a function of temperature was not observed in other members of the LnAlP n family so far [31,33,35,41]. It was previously observed in just a few materials, such as the chargetransfer salts [58] and SmSb [59]. In the first case, the sudden decrease of the amplitude with decreasing temperature was associated with the presence of highly metallic edge states related to the quantum Hall effect in quasi-two-dimensional materials [58], which is unlikely to be the cause for the behavior found in CeAlSi.…”
supporting
confidence: 61%
“…In the first case, the sudden decrease of the amplitude with decreasing temperature was associated with the presence of highly metallic edge states related to the quantum Hall effect in quasi-two-dimensional materials [58], which is unlikely to be the cause for the behavior found in CeAlSi. In the latter system, a sudden decrease of the Shubnikov-de Haas oscillations takes place once the material becomes antiferromagnetic, which could be caused by a nontrivial Berry phase [59]. Similarly to CeAlSi, the unusual behavior of the QO amplitude also appears in connection with a magnetically ordered phase.…”
mentioning
confidence: 96%
“…Recent attention is given to the NaCl-type rare-earth monopnictide RPn (R = rare earth; Pn = Sb, Bi) family [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], which are predicted to be promising correlated topological semimetal candidates [24,27]. RPn are always identified as compensated semimetals in the electronic structure aspect, where the conduction and valence bands are constituted by the 5d t 2g state of R and 3/2 p state of Pn, and lie at the X and points in the first Brillouin zone, respectively [28].…”
Section: Introductionmentioning
confidence: 99%
“…Searching for correlated and magnetic materials with topologically non-trivial electronic structures has recently led to the discovery of novel topological phases, such as topological Kondo insulators [1,2], magnetic topological insulators [3][4][5][6], magnetic Weyl semimetals [7][8][9][10] and Weyl-Kondo semimetals [11,12]. The LnX series crystallizing in the cubic NaCl-type structure [13](Ln = rare-earth and X = As, Sb or Bi) is a large family of semimetals where topologically nontrivial band structures have been found to exist with electronic correlations and magnetism [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. For example, evidence was found that CeSb hosts Weyl fermions in the fieldinduced ferromagnetic state [14], while NdSb was reported to be a Dirac semimetal with antiferromagnetic (AFM) order [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, evidence was found that CeSb hosts Weyl fermions in the fieldinduced ferromagnetic state [14], while NdSb was reported to be a Dirac semimetal with antiferromagnetic (AFM) order [25][26][27]. Meanwhile in SmSb, the analysis of the Shubnikov-de Haas (SdH) oscillations indicates a topologically non-trivial band structure [29]. Topological electronic structures were detected using angle-resolved photoemission spectroscopy (ARPES) for several rareearth mono-bismuthides (Ce, Pr, Sm, Gd)Bi, showing tunable bulk band inversions and corresponding surface states [30], where the ARPES results agree well with density functional theory (DFT) calculations assuming the 4f -electrons to be well localized [32].…”
Section: Introductionmentioning
confidence: 99%